1993
DOI: 10.1016/0014-5793(93)81283-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of homocysteine thiolactone by methionyl‐tRNA synthetase in cultured mammalian cells

Abstract: Homocysteine thiolactone is a product of an error-editing reaction, catalyzed by Escherrchiu colr and Saccharomyces cerevrsiae methionyl-tRNA synthetases, which prevents incorporation of homocysteine into tRNA and protein both in vitro and in vivo. Here, homocysteine thiolactone is also shown to be synthesized by cultured mammalian cells such as human cervical carcinoma (HeLa), mouse renal adenocarcinoma (RAG), and Chinese hamster ovary (CHO) cells labeled with ['5S]methionine, but not by normal human and mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 20 publications
3
91
0
1
Order By: Relevance
“…Similar ratios of deacylating and synthetic activities involving cognate substrates have been observed with other tRNAs and synthetases (10,18,19). Because of a relative slowness of enzymatic deacylation, in each case other explanations for the origin of the observed deacyaltion of aminoacyl-tRNA, in particular a possibility of a contaminating enzyme, must be ruled out.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Similar ratios of deacylating and synthetic activities involving cognate substrates have been observed with other tRNAs and synthetases (10,18,19). Because of a relative slowness of enzymatic deacylation, in each case other explanations for the origin of the observed deacyaltion of aminoacyl-tRNA, in particular a possibility of a contaminating enzyme, must be ruled out.…”
Section: Resultssupporting
confidence: 65%
“…Homocysteine is misactivated by methionyl-tRNA synthetase at unacceptably high level (4-6) but then cyclized to homocysteine thiolactone (7) to prevent transfer to tRNAMet both in vitro (5,7) and in vivo (8)(9)(10). Because of limited selectivity of the editing site of methionyl-tRNA synthetase, some of the cognate substrate methionine is also cyclized to a corresponding thiolactone, S-methyl homocysteine thiolactone (1 1).…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggests that the methylation reaction is essential and we propose that, in the absence of methylation, Hcy-tRNA is hydrolysed to produce homocysteine thiolactone. Notably, previous studies have shown that homocysteine thiolactone formation is especially high in cells defective in methionine metabolism [3].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolysis of homocysteinyl-AMP gave rise to homocysteine thiolactone and AMP [2]. Based on this and other experiments in i o, it was postulated that the formation of large quantities of homocysteine thiolactone by several types of malignant cells is due to the proofreading activity of Met-tRNA synthetase [3]. Misactivation was measured by measuring the thiolactone formed.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation